Faktor-Faktor Yang Mempengaruhi Kepercayaan Nasabah Menabung Pada BNI KCP Panakkukang Mas Makassar: indonesia - Verawaty, Verawaty; Muchsidin, Feronica Fungky; Singkeruang, A. We Tenri Fatimah; Muchsidin, Murdin; Akbar, Hidayani (Movere Journal, 2024)
This study aims to analyze what factors influence customer confidence in saving at Bank BNI Panakkukang Mas Makassar by distributing questionnaires to customers of Bank BNI Panakkukang Mas Makassar. The analysis method used is Mean analysis by looking at the resulting average value. In this study, researchers distributed questionnaires to samples and the results were processed using the help of the SPSS 22 program. The results of the mean analysis show that reliability and care are more dominant in influencing customer confidence in saving at Bank BNI Panakkukang Mas Makassar where it can be seen from the mean value of reliability of 4.25 and care of 4.25 while for honesty of 4.24 and credibility of 4.22.